Split GFP technologies to structurally characterize and quantify functional biomolecular interactions of FTD-related proteins - Foglieni, Chiara (Sci Rep, 2017)
Protein multimerization in physiological and pathological conditions constitutes an intrinsic trait of proteins related to neurodegeneration. Recent evidence shows that TDP-43, a RNA-binding protein associated with frontotemporal dementia and amyotrophic lateral sclerosis, exists in a physiological and functional nuclear oligomeric form, whose destabilization may represent a prerequisite for misfolding, toxicity and subsequent pathological deposition. Here we show the parallel implementation of two split GFP technologies, the GFP bimolecular and trimolecular fluorescence complementation (biFC and triFC) in the context of TDP-43 self-assembly. These techniques coupled to a variety of assays based on orthogonal readouts allowed us to define the structural determinants of TDP-43 oligomerization in a qualitative and quantitative manner. We highlight the versatility of the GFP biFC and triFC technologies for studying the localization and mechanisms of protein multimerization in the context of neurodegeneration.